Digital TV rollout [US digital terrestrial TV]. - Fox, B. (IEEE spectrum)
The author examines whether the United States has got it wrong with digital terrestrial TV since, today, new digital terrestrial network services in the US are creating little interest, receivers are expensive and sales slow